BIMARISTANS OF THE EUPHRATES PENINSULA REGION, AND THEIR THERAPEUTIC ROLE IN ZENGID AND AYYUBID ERAS - Siddiq, Kazhin; Mohammed , Shawkat (Humanities Journal of University of Zakho, 2024)
Bimaristans are public facilities focused on providing therapeutic and medical services to patients. Many hospitals and bimaristans spread throughout the cities of the Euphrates Peninsula under Zengid and Ayyubid control, similar to the rest of the other Islamic cities. Their establishment and the interest in them accompanied the development of Islamic society and its urban growth. Various factors emerged in Euphrates Peninsula region during the sixth and seventh centuries AH, such as crises and natural disasters, and the frequent wars that contributed to increasing the interest of the Zengid and Ayyubid in health care services. Various bimaristans were established to provide treatment for patients, and they also served as advanced educational centers, in which students were taught medical theoretical and applied sciences.The rulers in the Euphrates Peninsula region sought to equip their hospitals with everything they needed, attaching pharmacies and medical bookstores to each of them. They also appointed a supervisor or director for each facility to supervise its management. Their advancement in this field impressed their Crusaders enemies, so they borrowed from them many treatment methods. Crusaders also imitated Muslims in building Islamic bimaristans. The research aims to review the bimaristans of the Euphrates Peninsula region that were established during the Zengid and Ayyubid eras. The most prominent factors that contributed to the interest in health care aspects at that time, the nature of the therapeutic services that the bimaristans provided to patients, and the most prominent doctors who served in them. The research is divided into three sections and a conclusion. The first section covers defining the bimaristans linguistically and terminologically, their types, and the system of work during Zengid and Ayyubid control. The second section discusses the most prominent factors that contributed to supporting and establishing the bimaristans in the Euphrates Peninsula region. The third and the final section focuses on the bimaristans of the Euphrates Peninsula region, and the most prominent doctors who worked there at that time.